2021
DOI: 10.1002/ange.202106812
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bond‐Driven Synergistically Enhanced Hyperpolarizability: Chiral Coordination Polymers with Nonpolar Structures Exhibiting Unusually Strong Second‐Harmonic Generation

Abstract: Four chiral coordination polymers (CPs), M[(S,S)‐C14H14N2O6] and M[(R,R)‐C14H14N2O6] (M=Zn or Cd), have been exclusively synthesized in high yields with the aid of newly designed chiral ligand under hydrothermal condition. The CPs crystallizing in the orthorhombic nonpolar space group, C2221, reveal three‐dimensional framework structures composed of MO4 tetrahedra and the corresponding homochiral linkers. Powder second‐harmonic generation (SHG) measurements indicate that the nonpolar CPs reveal very strong SHG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…1100–1300 and 750–870 cm −1 regions confirm the presence of the C–O stretching and the C–H bending of para -aromatic groups. 33,37,48–50 In addition, peaks found at 690–740 and 480–670 cm −1 are attributable to NbO and Nb–F vibrations, respectively. 51,52 The IR spectra for the title compounds can be found in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1100–1300 and 750–870 cm −1 regions confirm the presence of the C–O stretching and the C–H bending of para -aromatic groups. 33,37,48–50 In addition, peaks found at 690–740 and 480–670 cm −1 are attributable to NbO and Nb–F vibrations, respectively. 51,52 The IR spectra for the title compounds can be found in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…30–32 Recently, our group has been quite successful in systematically synthesizing a series of novel NCS organic–inorganic hybrid materials or coordination compounds by utilizing chiral structure-directing agents or chiral ligands. 33–37 In this work, we have successfully grown huge crystals of two NCS hybrid niobium oxyfluorides, ( R )-[C 8 H 10 NO 3 ] 2 [NbOF 5 ] [( R )-Nb] and ( S )-[C 8 H 10 NO 3 ] 2 [NbOF 5 ] [( S )-Nb], by introducing carefully controlled chiral templates, 4-hydroxy- d -(−)-2-phenylglycine [( R )-HPG] and 4-hydroxy- l -(+)-2-phenylglycine [( S )-HPG]. We found that the crystals exhibit large birefringence (Δ n exp ) of 0.19–0.199@589.3 nm; thus, the origin of the large optical anisotropy is elucidated through a more detailed analysis.…”
Section: Introductionmentioning
confidence: 99%
“…12–14 Chiral templates inherently belong to the NCS crystal system, allowing them to exhibit NLO characteristics and hold promise for optical applications. 15…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Chiral templates inherently belong to the NCS crystal system, allowing them to exhibit NLO characteristics and hold promise for optical applications. 15 In general, NCS compounds containing stereochemically active lone pair cations are more likely to exhibit second har-monic generation (SHG) response [16][17][18] and significant birefringence. 19,20 However, a critical issue concerns the stability of Sn(II) ions, which are prone to disproportionation, leading to products with Sn(0) and Sn(IV) oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…A number of efforts have been made to improve the probability of functional NLO materials with NCS structures. 4–6 Among many, one promising approach has been considered to introduce the so called NCS chromophores such as second-order Jahn–Teller distortive cations (Pb 2+ , Sb 3+ , Ti 4+ , Mo 6+ , etc. ), 7–10 greatly polarizable d 10 metal cations (Zn 2+ , Cd 2+ , etc.…”
Section: Introductionmentioning
confidence: 99%